IMPROVING QUOTATION PROCESS BY VALUE STREAM MAPPING - Zhu, Lei (My University, 2014)
In the manufacturing companies, more than 50 percent of the total customer lead times are happened between receiving an order and releasing it to the shop floor, however, this part has been neglected mostly in the organization. The purpose of this paper is to identify possible reasons causing lower effective outcome in the current workflow in the quotation process. Since the lean production has mainly been studied in the manufacturing business, it is critical to understand whether the same principle in the manufacturing sector can be brought to knowledge work in the office. It is also essential to recognize factors which seen as wastes and influence to value to the end customer in the organization. Different theories are adopt-ed to form the theoretical background for this research to discuss specific aspects of knowledge work. Then the empirical part is approached by adopting value stream mapping in the case company. This is to execute by identifying wastes and analyzing current process and provide improvement ideas. The research methodology is deductive research. Interview were conducted as semi-structured interviews and also other materials provided by all departments. The result of this research reveal the non-value added activities in the current workflow have much influenced the response time towards quotation process. The proposed implementation plan is to meet the requirement that expected outcome in case company. As well, collaborative awareness of cooperation of several functional departments is strengths to create of continuous improvement.
Keywords: lean; value stream mapping; waste; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|